Developing an Inquiry-Based E-LKPD Integrating Mathematics and Science to Enhance Problem-Solving Skills among Madrasah Ibtidaiyah Students - Ummah, Risalul; Moh. Anang Abidin; Rofiqoh Nirwana; Wachyudi Achmad; Feri Kuswanto (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2026)
This study is based on the low level of students’ problem-solving skills, which is caused by the lack of optimal integration between mathematics and science learning and the limited use of interactive digital media in Madrasah Ibtidaiyah. The purpose of this study is to develop an inquiry-based E-LKPD that integrates mathematics and science in order to improve students’ problem-solving skills. The method used in this study is Research and Development (R&D) with the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The trial was conducted at MINU Durungbedug and MI At-Taqwa Sukodono. Data were collected through expert validation sheets, learning outcome tests, observations, and student response questionnaires. Data analysis was carried out through validity testing, paired sample t-tests, and N-Gain calculations. The results of this study indicate that the product feasibility level reached 90.6%, which falls into the very valid category. The results of the t-test showed a significant improvement in students’ problem-solving skills, while the N-Gain values of 0.56 and 0.55 were categorized as moderate. Thus, the developed E-LKPD is considered valid, practical, and effective in supporting inquiry-based learning in Madrasah Ibtidaiyah.